The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011 International Electron Devices Meeting 2011
DOI: 10.1109/iedm.2011.6131680
|View full text |Cite
|
Sign up to set email alerts
|

High performance n-MOS finFET by damage-free, conformal extension doping

Abstract: A solution for conformal n-type finFET extension doping is demonstrated, yielding I ON values of 1.23 mA/µm at I OFF =100 nA/um at 1V. This high device performance results from 40% reduced external resistance, which in term is stemming from 130% increased fin sidewall doping (confirmed by SIMS, SSRM and Atom Probe) relative to ion implant process. In this work we also report lowered gate leakage due to the damagefree extension doping. Introduction and need for conformal doping

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…It also suffers from implanting multiple species with multiple energies in a single process which can be a problem when a high level of control is required. 30,31 Our MOVPE approach is presented as an alternative methodology, based on surface in-diffusion, providing a conformal and nondestructive solution for semiconductor doping of non-planar structures and devices.…”
Section: Figmentioning
confidence: 99%
“…It also suffers from implanting multiple species with multiple energies in a single process which can be a problem when a high level of control is required. 30,31 Our MOVPE approach is presented as an alternative methodology, based on surface in-diffusion, providing a conformal and nondestructive solution for semiconductor doping of non-planar structures and devices.…”
Section: Figmentioning
confidence: 99%
“…Classical standard doping techniques like ion implantation may not be suitable for FinFET devices because of the 3D geometry. Several solutions to incorporate dopants in the fin are being explored such as tilted ion implantation [23,153,158], plasma doping [159][160][161][162] or vapor phase doping [163]. Among them, tilted ion implantation remains a strong candidate to introduce dopants into the fin, as it is a conventional and well established technique, although it suffers from specific issues that arise from the particular geometry of these devices.…”
Section: Doping Issues In Finfet Devices: a Challenge In 3dmentioning
confidence: 99%
“…In fact, the lateral diffusion of the dopants into the channel under the gate (gate overlap) is an important parameter that affects the final device performance [160]. This lateral diffusion has been also analyzed by KMC simulations in Fig.…”
Section: Doping Conformalitymentioning
confidence: 99%
See 1 more Smart Citation
“…This technique enables very shallow conformal doping. [15][16][17] Trenches between the fin arrays were filled by off-line processing. Our APT results indicated that the peak boron concentration in the fin sidewall regions was above 3 Â 10 20 atoms/cm 3 , which is higher than the activation level of 1 Â 10 20 atoms/cm 3 by spike and rapid thermal annealing.…”
mentioning
confidence: 99%